Odpowiedzi

2010-02-16T15:00:40+01:00
-3-3(2x-2)=3(x-2)
-3-6x +6= 3x-6
-6x-3x=-6-6+3
-9x=-9
x=1


2x-(8-x)=-2(x-5)
2x-8+x=-2x+10
2x+x+2x=10+8
5x=18
x=3,6


2/3x- 4 2/3= 2x-6
2/3x - 2x = -6+4 2/3
2/3x - 2/1x = 6/1+14/3
2/3x - 6/3x= -18/3+14/3
-4/3x= -4/3
x=1



-5x+2(1-x)= -x-2(x+1)
-5+2 - 2x= -x - 2x -2
-5x - 2x+ 2x +x= -2-2
-4x=-4
x=1

1 5 1
Najlepsza Odpowiedź!
2010-02-16T15:00:59+01:00
-3-3(2x-2)=3(x-2)
-3-6x+6=3x-6
-6x-3x=-6+3-6
-9x=-9 /:(-9)
x=1

2x-(8-x)=-2(x-5)
2x-8+x=-2x+10
2x+x+2x=10+8
5x=18 /:5
x=3,6

⅔x-4⅔=2(x-3)
⅔x-4⅔=2x-6
⅔x-2x=-6+4⅔
-4/3x=-4/3 /:(-4/3)
x=1

-5x+2(1-x)=-x-2(x+1)
-5x+2-2x=-x-2x-2
-5x-2x+x+2x=-2-2
-4x=-4 /:(-4)
x=1
2010-02-16T15:06:26+01:00
-3-3(2x-2)=3(x-2)
-3-6x+6=3x-6
-6x-3x=-6+3-6
9x=9/;9
x=1


1 3 1